Synthesis of Highly Basic Hexasubstituted Biguanides by Environmentally Friendly Methods - Glasovac, Zoran; Trošelj, Pavle; Jušinski, Iva; Margetić, Davor; Eckert-Maksić, Mirjana (Synlett, 2013)
A series of hexasubstituted biguanides was synthetized employing nonconventional and environmentally friendly methods. Their properties were studied computationally (basicity) and experimentally (basicity and catalytic properties in transesterification reaction).
Keywords: guanidines; superbases; green chemistry; solid-phase synthesis; nucleophilic addition; catalysis